Impact of Breastfeeding Duration on Infant Health Outcomes in Türkiye: A Cross-Sectional Analysis - Öykü ÖZBÖRÜ AŞKAN; İlker KAYI (Namık Kemal Tıp Dergisi, 2025)
Aim: The present study aims to examine the relationship between breastfeeding duration and health outcomes among children aged 12-24 months in Türkiye to provide evidence-based recommendations for improving public health strategies and better breastfeeding practices. Materials and Methods: This study relies on data from the Turkish Statistical Institute, Türkiye Health Survey 2022 dataset on children aged 0-14 years. The dataset contains information about breastfeeding duration and the health outcomes in children. Health outcomes, including general health status, chronic diseases, restrictions in daily life, and infectious diseases were analyzed using the chi-square and Mann-Whitney U tests. A p-value of <0.05 was considered statistically significant. Results: Among the 343 infants aged between 12 and 24 months, 83% were breastfed for at least six months and 65% for at least 12 months. Infants who were breastfed for six months or longer were found to have better health status (p=0.021), lower rates of chronic diseases (p=0.042), and fewer restrictions in daily life (p=0.014). Breastfeeding for at least six months was associated with reduced history of communicable diseases (p=0.026) and lower respiratory tract infections (p=0.010). No significant differences were observed for acute gastroenteritis or urinary tract infections. Breastfeeding for a period longer than 12 months was associated with lower communicable disease history (p=0.047). Conclusion: Our study highlights the significant benefits of breastfeeding. Particularly breastfeeding at least for 6 months was associated with improved infant health outcomes and reduced history of acute and chronic diseases in early childhood.